ESCORE DE AGITAÇÃO (EA) DE BEZERROS NELORE - BARBOSA, Taciara Aparecida Duarte,; SOUZA, Andrea Roberto Duarte Lopes,; OLIVEIRA, Pedro Henrique Pereira,; VILELA, Reíssa Alves,; SANTOS, Tânia Mara Baptista, (ANAIS DO ENIC, 2024)
-